The Role of Strategic Intelligence in Fulfilling the Dimensions of the Entrepreneurial University Model According to the Guiding Framework of the European Commission and the Economic Cooperation Organization: An Applied Study at King Khalid University - Osman, Anjom Ahmed (The Arab Journal of Administration, 2025)
The study aimed to identify the availability of strategic intelligence dimensions and its impact on the availability of the dimensions of the entrepreneur university model in accordance with the guiding framework of the European Commission and the Economic Cooperation Organization at King Khalid University, using the descriptive analytical approach, and to achieve the goal, field data was collected through a questionnaire that was distributed to the study community, (283) valid questionnaires were retrieved for analysis that was analyzed statistically, The study reached a set of results (according to the opinions of the study sample), the most important of which were: the availability of the dimensions of strategic intelligence and the dimensions of the entrepreneur university model to a large degree, and the presence of a statistically significant effect at the level of significance (0.05) for the dimensions of strategic intelligence on the dimensions of the entrepreneurial university model, and the absence of statistically significant differences for the respondents’ views towards the level of meeting the dimensions of strategic intelligence at the university attributed to the variables (job, academic degree), with statistically significant differences for the respondents’ views towards the level of meeting the dimensions of the university model Entrepreneurship is attributed to the variables (job, academic degree). Accordingly, the researcher presented a set of recommendations, the most important of which were: the university’s continuation in improving the practices and fulfillment of the dimensions of strategic intelligence by educating its leaders about its importance and role in promoting and developing strategies that support entrepreneurship and innovation at the university, and supporting entrepreneurship teaching and learning activities by teaching entrepreneurship to students, developing their mentalities and skills, and stimulating their entrepreneurial intentions by offering courses in the field of entrepreneurship as compulsory courses within the university’s requirements.